Machine Parameter Optimization For Wire-Electric Discharge Machining - F. R. M., Romlay; Asmizam, Mokhtar (2008)
This paper presents an optimization of the wire-Electric Discharge Machining (EDM) cutting parameter at welding joint area. The experiment is conducted during a gear shape optimization process by reducing the gear material and weight. Some area of the gear is welded for material joining process. The wire-EDM cutting process is conducted by cutting at the single material and welding area. The parameters of cutting process such as wire speeds, wire tensions and wire voltage are considered to be optimized. The cutting condition at the single and double materials area is compared. The result of the experiment shows that the cutting speed of the wire-EDM is affect by cutting parameters changing.